Comparison between Hormone and Porcine Follicular Fluid Secretion Supplements on In vitro Oocyte Maturation - Gumlungpat, Nongnuch; Youngsabanant, Mayuva; Rattanayuvakorn, Sukjai (Thai Journal of Science and Technology, 2023)
The aimed of the study to comparison between using porcine ovarian follicular fluid secretion and FSH, LH and estradiol and 10% fetal bovine serum (FBS) to supplement development of porcine oocytes cultured in the laboratory. Porcine ovarian follicular fluid secretion from Large Write Pigs’ medium-sized oocytes (4-6 mL) at concentrations of 200 and 500 µg protein/mL per porcine oocyte embraced by medium-sized oocytes cultured in the 37 oC sterile-conditioned thermos incubator with 5% high humidity and 95% CO2 in the atmosphere, supplemented by 2.2 mg/mL M199, 0.25 mM NaHCO3, 15 µg/mL and 50 µg/mL pyruvate as well as gentamicin sulfate. There were 4 groups: Group 1, oocytes cultured in M199; Group 2, oocytes cultured in M199 supplemented with hormones (LH, FSH and estradiol); Group 3, oocytes cultured in M199 supplemented with hormones and 10% HTFBS; and Group 4, oocytes cultured in M199 supplemented with fluid secretion from medium-sized porcine oocytes with 200 and 500 µm/mL protein concentrations. The result of cultures, performed for 24 and 44 h by measuring the diameter of oocytes which had sizing extension as growing, disclosed that the secretion from medium-sized oocytes with a 200 µg/mL concentration didn’t give an impact on the growth of surrounding cells, while that with a 500 µg/mL concentration did, leading to a significantly higher growth percentage than that of the positive control (supplemented by hormones and bovine serum), statistically. The surrounding cells extended and turned more fibroblastic than the positive control. This can be concluded that the secretion from medium-sized oocytes with a 500 µg/mL concentration was the most appropriate supplement to be used in the culture medium to assist oocyte development in place of costly hormones and bovine protein serum.